Application of Contextual Teaching And Learning (CTL) Model to Improve Learning Outcomes and Critical Thinking Ability in Redox and Electrochemical Material for Class XII SMA - Surya Firdausy; Deni Ainur Rokhim; Hayuni Retno Widarti (Jurnal Pendidikan dan Pembelajaran Kimia, 2020)
Abstract: application of Contextual Teaching and Learning (CTL) model to ImproveLearning Outcome and Critical Thinking Ability in Redox and Electrochemical Topics of Grade XII of SMA. The Contextual Teaching and Learning (CTL) model teaches the steps used in improving critical thinking and this study uses CTL based teaching materials for redox and electrochemical materials. The purpose of this study is to find out; (1) the implementation of CTL and conventional learning (2) the difference in the critical thinking ability of the CTL class with the conventional class, (3) the difference in CTL class learning outcomes with the conventional class, (4) the students' response to the CTL based teaching materials. The research design used was quasiexperimental or Quasi Experimental Design with Posttest Only Control Design. The results showed that: (1) The implementation of CTL learning had an average of 86% and conventional learning was 85%. (2) There is a difference in students' critical thinking skills with the average experimental class (66.93) higher than the control class (51.32). (3) There are differences in student learning outcomes with the average experimental class (64.93) higher than the control class (48.89). (4) Students' responses to CTL based teaching materials based on the results of the assessment of students by 76% to assess the content of teaching materials and for an assessment of its users by 72%. Both are classified as good use in this study although based on comments, obstacles, and suggestions that these teaching materials have strengths and weaknesses that need to be corrected for future users.Keywords: Contextual Teaching and Learning (CTL), critical thinking skills, learningoutcomes, redox reactions and electrochemistry.